Message of the special issue in the public agency The sign of Faqih Zayn al - Din bin Najim Hanafi Study and investigation - Saihood, Hasan Muhsin (Al-Adab Journal, 2018)
This research is a study and investigation of an important subject in the jurisprudence of Abu Hanifa, which is the issue of the Agency. It was divided into two sections: a class, a definition of the author, his scientific efforts, and how to achieve the text.